Design and evaluation of IKK-activated GSK3β inhibitory peptide as an inflammation-responsive anti-colitic therapeutic. (1st September 2021) - Hong, Sungchae; Ju, Sanghyun; Yoo, Jin-Wook; Ha, Nam-Chul; Jung, Yunjin
Abstract : Colon-targeted cell-permeable IKK-activated GSK3β inhibitory peptide (CTP-IAGIP in a colon-targeted capsule) is an inflammation-responsive anti-colitic therapeutics. Abstract : Glycogen synthase kinase-3β (GSK3β), a multi-functional kinase, is a promising therapeutic target for the treatment of inflammation. Inhibitory κB kinase (IKK)-activated GSK3β inhibitory peptide (IAGIP) was designed as an inflammation-responsive anti-colitic therapeutic. To optimize therapeutic efficiency, IAGIP was tested using two different drug delivery techniques: colon-targeted delivery and cell-permeable peptide modification. In cell-based experiments, in response to tumor necrosis factor (TNF)- and lipopolysaccharide (LPS)-mediated activation of IKK, cell-permeable IAGIP (CTP-IAGIP) inhibited GSK3β, leading to increased production of anti-inflammatory cytokine interleukin-10 (IL-10) and suppression of TNF- and LPS-induced NFκB activity. Oral gavage of CTP-IAGIP loaded in the colon-targeted capsule attenuated 2, 4, 6-trinitrobenzene sulfonic acid-induced rat colitis and lowered the expression levels of NFκB-regulated proteins in the inflamed colons. CTP-IAGIP further induced IL-10 production in the inflamed colonic tissues; however, the levels of IL-10 were not affected in the normal colonic tissue or colonic tissue in which inflammation had subsided. Collectively, our data suggest that IAGIP administered using the aforementioned drug delivery techniques is an orally active anti-colitic drug selectively responding to inflammation.